UPACARA ADAT BUANG JUNG pada Masyarakat Suku Sekak di Bangka - Fajriana, Fidyan (Fakultas Ilmu Budaya Universitas Diponegoro, 2008)
Rules, norms, views, traditions or customs embody social system supporters, who later formed the customary tradition. One of the customs is a traditional ceremony of Buang Jung conducted by fisherman’s community in Bangka Island. The ceremony was carried out because of the belief in forces beyond human abilities such as God of the Sea. This ceremony is called Buang Jung (meaning boat offering), since a jung (mini boat) is thrown into the sea as an offering of Sekak Tribe to the god of the sea.